The Effect of The Tax System, Tax Audit, And Tax Sanctions Compliance with The Corporate Taxpayer at The Tax Service Office Primary Makassar West - Lina Mariana (Golden Ratio of Taxation Studies, 2021)
Aim study this is for analyze influence system taxation, inspection tax, and penalty taxation to obedience must tax body. Amount must tax from year to year the more increase. However the increase in the number of taxpayers is not matched by taxpayer compliance in paying taxes. Problem obedience the Becomes constraint in maximization reception tax. Study this study level obedience must tax body which registered in region KPP Primary Macassar West with use a number of independent variables, namely the tax system, tax audit, and tax sanctions. Data used in This research is the primary data obtained from the research location, namely through the distribution of questionnaires or questionnaire (list question to respondent). Sample consists from 97 respondent which is must tax body active as well as secondary data obtained from KPP Pratama West Makassar which is closely related to research this. Data were tested using multiple linear regression analysis. Testing the data using SPSS 22. Researcher also conducted a validity test and reliability test for the questionnaire. The classic assumption test used is the test multicollinearity, test normality, and test heteroscedasticity. For testing hypothesis researcher use coefficient of determination (R2), Simultaneous test (F-test), and partial test (t-test). Based on the results of the analysis performed it is concluded that the tax system, tax audit, and tax sanctions have an influence positive and significant towards compliance taxpayer body at KPP Makassar Primary West.